Finn, Bride and Walsh, Babe 2. Interview about fairy lore. - Tennier-Stuart, Emma (2014)
Emma Tennier-Stuart interviewing Bride Finn and Babe Walsh in the Alderwood Estates retirement home about fairy lore in Witless Bay, Newfoundland. Recorded by Andrea McGuire 0:00 – Bride Finn's daughter saw a ghost that she thought was her great-grandfather, but may have been her great-uncle; 0:50 – Would BF need to see a ghost or fairy to believe in them? BF believes, but isn’t sure; there has to be something, because her daughter wouldn’t lie to her; “They’re not here to hurt you; they’re only passing through.”; 1:30 – BF prayed for rest for their souls; 1:40 – Daughter saw a ghost sitting in her room